Peran Keterlibatan Siswa dalam Implementasi Pembelajaran Teaching Factory Terhadap Kesiapan Kerja Siswa di SMKN 1 Jatibarang - Indramayanti, Vivi Silvi; Hasanah, Enung; Sudarsono, Bambang (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Vocational Secondary Education creates graduates who are ready for employment in the labor market, aligned with the competencies and industry requirements of their fields. The implementation of the Teaching Factory has proven to be a solution for equipping students with the skills and knowledge necessary for entering the workforce. This study aims to analyze the role of student involvement in the implementation of the Teaching Factory in enhancing the job readiness of students at State Vocational High School 1 Jatibarang. A qualitative descriptive method was employed. The research was conducted at State Vocational High School 1 Jatibarang, with data collected through in-depth interviews, observations, and documentation. The findings revealed that student involvement in the learning process through the Teaching Factory implementation significantly affects their skills, both soft and hard skills, regarding job readiness. Direct student engagement enhances the mastery of technical competencies, such as production processes and services, proficiency in skills relevant to their field, and understanding of standard operating procedures. Furthermore, the development of non-technical abilities equips students with skills in communication, teamwork, and problem-solving. Thus, student involvement in the learning process plays a crucial role in the job readiness of vocational school graduates, enabling them to integrate into the workforce.